Identification of cords by Mycobacterium kansassi and its implications in clinical microbiology - Rojas Jaimes, Jesús (2023)
Objectives: To determine if cord formation occurs in microcolonies of M. kansassi. Methods: Four species of highly prevalent pathogenic mycobacteria were seeded in the solid medium 7H11; Mycobacterium kansassi, Mycobacterium abscessus, Mycobacterium tuberculosis y Mycobacterium neonarum and observed for 21 days performing the Ziehl- Neelsen stain. Inverted light microscopy was used to detect cord formation. Results: All species produced cords, Mycobacterium kansassi, Mycobacterium abscessus, Mycobacterium tuberculosis y Mycobacterium neonarum at earlier stages of their growth detected by Ziehl-Neelsen. Conclusions: M kansasii is able to develop cords at microscopic levels indicating that this property is not distinctive of M tuberculosis as was originally thought.